A New CFAR Detector Based on Automatic Censoring Cell Averaging and Cell Averaging - Yuhua Qin; Huili Gong; Ting Liu (Institute of Advanced Engineering and Science, 2013)
In order to improve the interference immunity of the detector, a new CFAR detector (ACGCA-CFAR) based on automatic censoring cell averaging (ACCA) and cell averaging (CA) is presented in this paper. It takes the greatest value of ACCA and CA local estimation as the noise power estimation. Under swerling II assumption, the analytic expressions of in homogeneous background are derived. In contrast to other detectors, the ACGCA-CFAR detector has higher detection performance both in homogeneous and nonhomogeneous backgrounds, while the sample sorting time of ACGCA is only quarter that of OS and ACCA. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2686